The Mediterranean coastal areas from watershed to the sea: interactions and changes Proceedings of the MEDCORE international conferenceFlorence, 10th-14th November 2005 - Scapini, Felicita (Proceedings e report, 2006)
This volume presents the Proceedings of the International Conference of the MEDCORE project held in Florence, Italy, in November 2005. The MEDCORE project "From river catchment areas to the sea: a comparative and integrated approach to the ecology of Mediterranean coastal zones for sustainable management", funded by the European Commission, was carried out from 2002 to 2005 by a consortium of researchers from European and Mediterranean partner countries. It focused on coastal areas, with particular attention to the interactions and links between the elements. The approach was characterised by multidisciplinary research and integration of expertise. This book contributes to the information flow originated by the project and the conference. Despite the variety of the contributions, they have been gathered into this single volume to construct a baseline for an innovative interdisciplinary perspective.